Carbon material with regulated holes as well as regulation method and application of carbon material
By regulating the pore structure of porous carbon materials, the hard carbon negative electrode material is formed, which solves the problem of insufficient electrochemical performance of existing porous carbon materials in sodium ion batteries, and improves high efficiency, stability and low temperature performance.
Patent Information
- Application Number
- CN202411555686.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
When used as the negative electrode material of sodium ion battery, the existing porous carbon materials have low efficiency, no breakthrough improvement in electrochemical performance, and poor performance in low temperature environments.
By mixing the carbon precursor, solvent and porous carbon material, heat treatment and carbonization treatment, the porous structure of the porous carbon material is regulated, and a hard carbon negative electrode material with excellent electrochemical properties is formed.
The high first-time Coulomb efficiency, low potential platform, excellent cycling stability and high rate performance of sodium ion battery negative electrode material is achieved, while maintaining excellent capacity and platform capacity at low temperatures.
Smart Images

Figure CN119409166A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary battery negative electrode materials, and in particular to a pore-regulated carbon material and a regulation method and application thereof. Background Art
[0002] With the continuous development of various portable devices, new energy vehicles and energy storage systems, there is an urgent need to find low-cost, high-performance clean energy. The operating voltage of the battery is determined by the voltage difference between the positive and negative electrodes, which requires the voltage of the negative electrode to be as low as possible. Therefore, it is very important to develop sodium ion battery negative electrode materials with low voltage platform, high first coulomb efficiency, good rate performance and cycle stability, which can lay the foundation for the successful construction of high-performance negative electrode materials with low potential and fast sodium storage for full batteries in the future.
[0003] After being processed, hard carbon materials have a rich closed-pore structure. When used as negative electrode materials for sodium ion batteries, sodium ions fill the closed pores and can produce an obvious low-potential platform. Porous carbon has low cost and high yield, and is widely used in supercapacitors. However, when it is used as a sodium ion battery, due to its developed porous structure and highly disordered lattice, it can only store sodium by adsorption, with only a slope, and the first coulombic efficiency is very low, so its pore structure needs to be adjusted. Some researchers use template carbonization, physical / chemical activation pore size control and other processes to adjust the pore size of carbon materials, and use pre-oxidation, material composite, vapor deposition and other methods to achieve the regulation of microcrystals. However, these schemes are complex to operate and have a single precursor. When used as negative electrode materials for sodium ion batteries, their electrochemical performance has not been improved significantly.
[0004] Therefore, it is of great significance to find a method to adjust the pore structure of hard carbon negative electrode materials for sodium ion batteries starting from porous carbon to improve the tap density, first coulombic efficiency and low-voltage platform performance of porous carbon negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a pore-regulated carbon material and a regulation method and application thereof, and to apply the pore-regulated carbon material to a negative electrode material of a sodium ion battery, which has high first coulombic efficiency, high rate performance, excellent cycle stability and a low potential platform.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for controlling the pores of a porous carbon material, comprising the following steps:
[0008] The carbon precursor, solvent and porous carbon material are mixed to obtain a mixed solution; the mixed solution is subjected to heat treatment and carbonization treatment in sequence to complete the pore regulation of the porous carbon material.
[0009] Preferably, the carbon precursor includes one or more of coal tar, petroleum tar, chitosan and phenolic resin;
[0010] The solvent includes one or more of tetrahydrofuran, xylene, n-hexane, ethanol and pyridine;
[0011] The specific surface area of the porous carbon material is 20 to 5000 m 2 / g.
[0012] Preferably, the mass volume ratio of the carbon precursor, the solvent and the porous carbon material is 1 g: 10-30 mL: 0.01-10 g.
[0013] Preferably, the heat treatment pressure is -0.01 to -10 MPa.
[0014] Preferably, the heat treatment temperature is 30-200° C., and the heat treatment time is 0.5-48 h.
[0015] Preferably, the carbonization treatment is carried out under an inert atmosphere, which is nitrogen or argon.
[0016] Preferably, the pressure of the carbonization treatment is -5 to 0.1013 MPa.
[0017] Preferably, the heating rate of the carbonization treatment is 0.5-20°C / min, the target temperature of the carbonization treatment is 1100-2000°C, and the insulation time after reaching the target temperature is 0.5-8h.
[0018] The present invention also provides a pore-regulated carbon material obtained by the pore-regulating method of the porous carbon material.
[0019] The present invention also provides the use of the pore-regulated carbon material in the negative electrode material of a sodium ion battery.
[0020] The beneficial effects of the present invention are:
[0021] The present invention provides a method for pore regulation of porous carbon materials, comprising the following steps: mixing a carbon precursor, a solvent and a porous carbon material to obtain a mixed solution; sequentially subjecting the mixed solution to heat treatment and carbonization treatment to complete pore regulation of the porous carbon material. The present invention regulates the pore structure of the porous carbon material to design and form a hard carbon negative electrode for use in the field of sodium ion batteries, thereby broadening the application field of porous carbon materials. The present invention can promote the small molecule carbon precursor in the solution to enter the near-surface pore structure of the porous carbon material through a specific heat treatment process (reduced pressure drying process), thereby regulating the pore volume, pore size and specific surface area without causing a coating layer to be formed between the two-phase interface and the surface.
[0022] The present invention has the property of changing the pore structure from outside to inside. On the one hand, the pore structure near the surface of the porous carbon material is appropriately closed by heat treatment (reduced pressure drying process), the pore size and specific surface area are regulated, and the hard carbon negative electrode of the sodium ion battery is obtained, and the slope sodium storage behavior is transformed into a low potential platform sodium storage behavior (the low-pressure platform capacity reaches 224mAh / g), and the coulomb efficiency is increased to 88% for the first time. On the other hand, the pore structure inside the porous carbon material is retained, which can promote Na + The diffusion behavior in the bulk phase of the material at low temperatures enables the obtained hard carbon material to exhibit excellent electrochemical properties at low temperatures, with a platform capacity retention rate of 100% at -10°C and a platform capacity retention rate of 85% at -20°C.
[0023] The present invention can control the pore type, pore volume, specific surface area, open pore size and surface interface state of the final carbon material by changing the type of carbon precursor, solution concentration, heat treatment temperature and pressure, and carbonization treatment temperature and heating rate. The regulated carbon material is conducive to the closed-pore filling of sodium ions, thereby optimizing battery performance. The obtained material is used as a negative electrode material for sodium ion batteries, which can achieve simultaneous and significant improvements in low potential platform, first coulomb efficiency, rate performance and cycle stability, and also has excellent capacity retention rate in a low temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a transmission electron microscope characterization image of the carbon material after pore control in Example 1;
[0025] Figure 2 The charge and discharge curve of the sodium ion battery in Example 1 at room temperature (Specific Capacity—specific capacity, Potential—voltage);
[0026] Figure 3 The charge and discharge curves of the sodium ion battery at different temperatures in Example 3 (Specific Capacity—specific capacity, Potential—voltage);
[0027] Figure 4 The charge and discharge curve of the sodium ion battery in Comparative Example 1 at room temperature (Specific Capacity—specific capacity, Potential—voltage);
[0028] Figure 5 It is a transmission electron microscope characterization image of the carbon material in Comparative Example 3;
[0029] Figure 6 The charge and discharge curve of the sodium ion battery in Comparative Example 3 at room temperature (Specific Capacity—specific capacity, Potential—voltage);
[0030] Figure 7 These are nitrogen adsorption and desorption curves of the carbon materials after pore control in Examples 1 to 4 (Relative Pressure—relative pressure, Adsorbed Volume—adsorbed volume). DETAILED DESCRIPTION
[0031] The present invention provides a method for controlling the pores of a porous carbon material, comprising the following steps:
[0032] The carbon precursor, solvent and porous carbon material are mixed to obtain a mixed solution; the mixed solution is subjected to heat treatment and carbonization treatment in sequence to complete the pore regulation of the porous carbon material.
[0033] In the present invention, the carbon precursor preferably includes one or more of coal tar pitch, petroleum tar pitch, chitosan and phenolic resin.
[0034] In the present invention, the solvent preferably includes one or more of tetrahydrofuran, xylene, n-hexane, ethanol and pyridine.
[0035] In the present invention, the porous carbon material is preferably activated carbon; the tap density of the porous carbon material is preferably 0.2 to 1 g / mL, more preferably 0.29 to 0.85 g / mL, and more preferably 0.37 to 0.56 g / mL; the specific surface area of the porous carbon material is preferably 20 to 5000 m 2 / g, more preferably 23 to 2915 m 2 / g, more preferably 1642 to 2187 m 2 / g.
[0036] In the present invention, the porous carbon material has a simple synthesis process and abundant raw material sources, but its pore structure is an open hole obtained by etching, and it is often used as a simple adsorbent or catalyst carrier; the present invention regulates the pore structure of the porous carbon material and designs a hard carbon negative electrode, which is suitable for the field of sodium ion batteries, thereby improving the high added value of the porous carbon material.
[0037] In the present invention, the mass volume ratio of the carbon precursor, the solvent and the porous carbon material is preferably 1g:10-30mL:0.01-10g, more preferably 1g:12-28mL:0.5-8g, and more preferably 1g:15-25mL:1-3g.
[0038] In the present invention, the mixing preferably includes the following steps: firstly, fully dissolving the carbon precursor in a solvent to obtain a carbon precursor solution, and then dispersing the porous carbon material in the carbon precursor solution to obtain a mixed solution.
[0039] In the present invention, the pressure of the heat treatment is preferably -0.01 to -10 MPa, more preferably -1 to -8 MPa, and even more preferably -2 to -5 MPa.
[0040] In the present invention, the heat treatment temperature is preferably 30-200°C, more preferably 60-150°C, more preferably 80-100°C; the heat treatment time is preferably 0.5-48h, more preferably 5-40h, more preferably 8-20h.
[0041] In the present invention, after the heat treatment is completed, the solid powder is collected and subjected to carbonization treatment.
[0042] In the present invention, the carbonization treatment is preferably carried out under an inert atmosphere, and the inert atmosphere is preferably nitrogen or argon.
[0043] In the present invention, the pressure of the carbonization treatment is preferably -5 to 0.1013 MPa, more preferably -3 to 0.1 MPa, and even more preferably -2 to -0.1 MPa.
[0044] In the present invention, the heating rate of the carbonization treatment is preferably 0.5-20°C / min, more preferably 3-18°C / min, and more preferably 5-15°C / min; the target temperature of the carbonization treatment is preferably 1100-2000°C, more preferably 1300-1900°C, and more preferably 1400-1700°C; the holding time after reaching the target temperature is preferably 0.5-8h, more preferably 2-6h, and more preferably 3-5h.
[0045] In the present invention, the carbonization treatment is preferably a staged temperature increase carbonization treatment. Specifically, the carbonization treatment comprises a first carbonization treatment and a second carbonization treatment performed sequentially. The temperature of the first carbonization treatment is preferably 1100-1300°C, more preferably 1150-1250°C, and more preferably 1200°C; the heating rate from room temperature to the temperature of the first carbonization treatment is preferably 5-20°C / min, more preferably 8-18°C / min, and more preferably 10-15°C / min; the temperature of the second carbonization treatment is preferably 1400-2000°C, more preferably 1500-1900°C, and more preferably 1600-1700°C; the heating rate from the temperature of the first carbonization treatment to the temperature of the second carbonization treatment is preferably 0.5-3°C / min, more preferably 1-2.5°C / min, and more preferably 1.5-2°C / min; the holding time after reaching the temperature of the second carbonization treatment is preferably 0.5-8h, more preferably 2-6h, and more preferably 3-5h.
[0046] In the present invention, a specific heat treatment process (reduced pressure drying process) can promote the small molecule carbon precursor in the solution to enter the near-surface pore structure of the porous carbon material, and adjust the pore volume, pore size and specific surface area without causing a coating layer to form between the two-phase interface and the surface; while the traditional chemical vapor deposition method, surface coating method and composite method will lead to the formation of a heterogeneous coating layer on the surface of the material, hindering the Na + The electrolyte diffuses into the interior of the material and produces a larger polarization phenomenon at the interface between the two phases.
[0047] The present invention also provides a pore-regulated carbon material obtained by the pore-regulating method of the porous carbon material.
[0048] The present invention also provides the use of the pore-regulated carbon material in the negative electrode material of a sodium ion battery.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1
[0051] Weigh 0.3 g of activated carbon (tap density of 0.56 g / mL, specific surface area of 23 m 2 / g), 0.1g coal tar; firstly, fully dissolve the coal tar in 2mL tetrahydrofuran to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat to 1200°C at a heating rate of 5°C / min, continue to heat to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0052] The pore-controlled carbon material prepared in this embodiment was characterized by transmission electron microscopy, and a transmission electron microscopy characterization image of the pore-controlled carbon material in this embodiment was obtained, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that there are a large number of short-range graphite microcrystal regions and closed-pore structures produced by microcrystal stacking in the carbon material after pore regulation.
[0053] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 25m 2 / g, tap density is 0.67g / mL, I D / I G The value is 1.42.
[0054] The sodium ion battery is prepared using the pore-regulated carbon material prepared in this embodiment, and the steps are as follows: weigh the pore-regulated carbon material, sodium carboxymethyl cellulose and carbon black in a mass ratio of 8:1:1, slurry them, apply them on copper foil, dry them and cut them to obtain battery electrodes. Then, the obtained battery electrode is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion battery in a glove box. The electrochemical performance is tested (the test adopts the CT2001A blue electric test system, and the temperature is room temperature 25°C), and the charge and discharge curve of the sodium ion battery in this embodiment at room temperature is obtained, as shown in FIG. Figure 2 As shown; Figure 2 In the figure, 1st is the charge-discharge curve of the first cycle, 2nd is the charge-discharge curve of the second cycle, and 3rd is the charge-discharge curve of the third cycle. Figure 2 It can be seen that the first coulombic efficiency of the material is 70.8%, with a low discharge / charge voltage platform (the low potential platform capacity is 224 mAh / g at a current density of 20 mA / g). The electrochemical performance test at low temperature shows that the reversible capacity of the material at -10°C is 218 mAh / g, of which the low potential platform capacity is 122 mAh / g.
[0055] Example 2
[0056] Weigh 0.2 g of activated carbon (tap density of 0.37 g / mL, specific surface area of 1642 m 2 / g), 0.2g coal tar, first dissolve the coal tar in 4mL tetrahydrofuran to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat to 1200°C at a heating rate of 5°C / min, continue to heat to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0057] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 54m 2 / g, the tap density is 0.69g / mL, and there are a large number of short-range graphite microcrystalline regions and closed-pore structures produced by microcrystalline stacking in the material. D / I G The value is 1.58.
[0058] The sodium ion battery was prepared using the pore-regulated carbon material prepared in this example, and the steps were the same as in Example 1. The electrochemical performance test showed that the material had a high first coulombic efficiency of 81%, a low discharge / charge voltage platform (the low potential platform capacity was 144 mAh / g at a current density of 20 mA / g); the reversible capacity retention rate was 91% after 50 cycles at a current density of 20 mA / g, and it had excellent cycle stability and high rate performance; the reversible capacity was 186 mAh / g at -10°C, of which the low potential platform capacity was 108 mAh / g.
[0059] Example 3
[0060] Weigh 0.1 g of activated carbon (tap density is 0.29 g / mL, specific surface area is 2187 m 2 / g), 0.2g coal tar, first dissolve the coal tar in 2mL tetrahydrofuran to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat to 1200°C at a heating rate of 5°C / min, continue to heat to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0061] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 40m 2 / g, the tap density is 0.70g / mL, and there are a large number of short-range graphite microcrystalline regions and closed-pore structures produced by microcrystalline stacking in the material. D / I G The value is 1.57.
[0062] The sodium ion battery was prepared using the pore-controlled carbon material prepared in this embodiment, and the steps were the same as in Example 1. The electrochemical performance was tested to obtain the charge and discharge curves of the sodium ion battery in this embodiment at different temperatures, as shown in FIG. Figure 3 As shown. Figure 3It can be seen that the material has a high first coulombic efficiency of 86%, a low discharge / charge voltage platform (the low potential platform capacity is 178 mAh / g at a current density of 20 mA / g), and a reversible capacity retention rate of 88% after 50 cycles at a current density of 20 mA / g, with excellent cycle stability and high rate performance; the reversible capacity at -10°C is 255 mAh / g, of which the low potential platform capacity is 185 mAh / g, the low potential platform capacity is completely maintained, and the platform capacity retention rate is 100%; the reversible capacity at -20°C is 216 mAh / g, of which the low potential platform capacity is 152 mAh / g, and the platform capacity retention rate is 85%.
[0063] Example 4
[0064] Weigh 0.1 g of activated carbon (tap density is 0.20 g / mL, specific surface area is 2915 m 2 / g), 0.2g coal tar, first dissolve the coal tar in 2mL tetrahydrofuran to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat to 1200°C at a heating rate of 5°C / min, continue to heat to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0065] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 46m 2 / g, the tap density is 0.69g / mL, and there are a large number of short-range graphite microcrystalline regions and closed-pore structures produced by microcrystalline stacking in the material. D / I G The value is 1.58.
[0066] The sodium ion battery was prepared using the pore-regulated carbon material prepared in this embodiment, and the steps were the same as in Example 1. The electrochemical performance test showed that the battery had a low discharge / charge voltage platform (the low potential platform capacity was 170 mAh / g at a current density of 20 mA / g); the reversible capacity retention rate was 84% after 50 cycles at a current density of 20 mA / g, and the battery had excellent cycle stability and high rate performance; the reversible capacity was 254 mAh / g at -10°C, of which the low potential platform capacity was 170 mAh / g, and the low potential platform capacity was completely maintained; the reversible capacity was 220 mAh / g at -20°C, of which the low potential platform capacity was 160 mAh / g, and both the total capacity and the platform capacity had high retention rates.
[0067] Example 5
[0068] Weigh 0.1 g of activated carbon (tap density is 0.29 g / mL, specific surface area is 2187 m 2 / g), 0.2g coal tar, first dissolve the coal tar in 2.5mL xylene to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat up to 1200°C at a heating rate of 5°C / min, continue to heat up to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0069] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 41m 2 / g, the tap density is 0.70g / mL, and there are a large number of short-range graphite microcrystalline regions and closed-pore structures produced by microcrystalline stacking in the material. D / I G The value is 1.58.
[0070] The sodium ion battery was prepared using the pore-controlled carbon material prepared in this example, and the steps were the same as in Example 1. The electrochemical performance test showed that the material had a high first coulombic efficiency of 88%, a low discharge / charge voltage platform, and a reversible capacity retention rate of 89% after 50 cycles at a current density of 20 mA / g, and had excellent cycle stability and high rate performance.
[0071] Example 6
[0072] Weigh 0.1 g of activated carbon (tap density is 0.29 g / mL, specific surface area is 2187 m 2 / g), 0.2g coal tar, first dissolve the coal tar in 4mL n-hexane to obtain a coal tar solution, then add activated carbon, stir to make it evenly dispersed, to obtain a mixed solution, heat-treat the mixed solution, and set the heat treatment conditions as follows: dry at -0.1MPa, 60°C in a vacuum drying oven for 8h. After the heat treatment, collect the solid powder, put it into a magnetic boat, and place it in a tubular furnace for carbonization treatment under a nitrogen atmosphere. Set the carbonization pressure to 0.1013MPa, heat to 1200°C at a heating rate of 5°C / min, continue to heat to 1500°C at a heating rate of 2°C / min, and keep warm at 1500°C for 2h to obtain a pore-controlled carbon material.
[0073] The surface of the carbon material after pore control prepared in this example is blocky, with a specific surface area of 43m 2 / g, the tap density is 0.71g / mL, and there are a large number of short-range graphite microcrystalline regions and closed-pore structures produced by microcrystalline stacking in the material. D / I G The value is 1.57.
[0074] The sodium ion battery was prepared using the pore-controlled carbon material prepared in this example, and the steps were the same as in Example 1. The electrochemical performance test showed that the material had a high first coulombic efficiency of 84%, a low discharge / charge voltage platform, and a reversible capacity retention rate of 86% after 50 cycles at a current density of 20 mA / g, and had excellent cycle stability and high rate performance.
[0075] Comparative Example 1
[0076] The other conditions in Example 3 are controlled to remain unchanged, and the heat treatment is performed in a blast drying oven at a pressure of 0.1013 MPa to obtain a carbon material.
[0077] The carbon material prepared in this comparative example has a block surface and a specific surface area of 46 m 2 / g, the tap density is 0.67g / mL, there are long-range graphite-like regions and a large number of porous structures in the material, I D / I G The value is 1.20.
[0078] The sodium ion battery was prepared using the carbon material prepared in this comparative example, and the steps were the same as those in Example 1. The electrochemical performance was tested to obtain the charge and discharge curve of the sodium ion battery in this comparative example at room temperature, as shown in FIG. Figure 4 As shown; Figure 4 In the figure, 1st is the charge-discharge curve of the first cycle, 2nd is the charge-discharge curve of the second cycle, and 3rd is the charge-discharge curve of the third cycle. Figure 4 It can be seen that the first coulombic efficiency of the material is 65%, and the low potential platform capacity is 110 mAh / g at a current density of 20 mA / g.
[0079] Comparative Example 2
[0080] Weigh 0.1 g of activated carbon (tap density is 0.29 g / mL, specific surface area is 2187 m 2 / g), 0.2g coal tar is added into a zirconia ball mill, and at the same time, 4 zirconia ball milling beads with a diameter of 6mm and 8 zirconia ball milling beads with a diameter of 12mm are put into the ball mill, and ball milled at a speed of 200r / min for 4h. After the ball milling, the materials are put into a magnetic boat and placed in a tubular furnace for carbonization treatment under a nitrogen atmosphere. The pressure of the carbonization treatment is set to 0.1013MPa, and the temperature is increased to 1200℃ at a heating rate of 5℃ / min, and then continued to be increased to 1500℃ at a heating rate of 2℃ / min, and kept at 1500℃ for 2h to obtain a carbon material.
[0081] The carbon material prepared in this comparative example has a block surface and a specific surface area of 85m 2 / g.
[0082] The sodium ion battery was prepared using the carbon material prepared in this ratio, and the steps were the same as those in Example 1. The electrochemical performance test showed that the low potential platform of the material was only 115 mAh / g, and the specific capacity was 249 mAh / g at a current density of 20 mA / g.
[0083] Comparative Example 3
[0084] Activated carbon (tap density of 0.29 g / mL, specific surface area of 2187 m 2 / g) was placed in a magnetic boat, placed in a tubular furnace under a nitrogen atmosphere for carbonization treatment, the pressure of the carbonization treatment was set to 0.1013 MPa, the temperature was increased to 1200°C at a heating rate of 5°C / min, and then the temperature was increased to 1500°C at a heating rate of 2°C / min, and the temperature was kept at 1500°C for 2h to obtain a carbon material.
[0085] The transmission electron microscope characterization diagram of the carbon material in this comparative example is as follows: Figure 5 As shown. Figure 5 It can be seen that the surface of the carbon material is blocky and has a specific surface area of 1766m 2 / g, the microcrystalline structure is highly disordered and the pore structure is well developed.
[0086] The sodium ion battery was prepared using the carbon material prepared in this comparative example, and the steps were the same as those in Example 1. The electrochemical performance was tested to obtain the charge and discharge curve of the sodium ion battery in this comparative example at room temperature, as shown in FIG. Figure 6 shown; from Figure 6 It can be seen that the first coulombic efficiency of the material is 20%, there is no low potential platform, and the specific capacity is only 100 mAh / g at a current density of 20 mA / g.
[0087] It can be seen from Examples 1 to 6 and Comparative Example 1 that only by adopting reduced pressure heat treatment can a pore-regulated carbon material be obtained. If a forced air drying oven is used for drying heat treatment, only a carbon material that is a simple mixture of porous carbon and asphalt can be obtained, which cannot achieve the effect of regulating the pore structure.
[0088] According to Examples 1 to 6, it should be noted that the porous carbon materials with different pore structures use different amounts of carbon precursors for pore regulation; the larger the specific surface area of the porous carbon material, the more developed the pore structure, and the more carbon precursors are required. If the amount of carbon precursors filled is too small, the pore structure cannot be completely filled; if the amount of carbon precursors filled is too large, a large amount of filling material will remain on the surface of the material, which will completely cover up the performance of the pore-regulated carbon material.
[0089] It can be seen from Examples 1 to 6 and Comparative Examples 1 to 3 that the carbon material after pore regulation according to the present invention has high first coulombic efficiency, good cycle stability and high low-voltage capacity compared with conventional carbon materials. When the carbon material after pore regulation obtained in Examples 1 to 6 is used as a negative electrode material for a sodium ion battery, the material has a high first coulombic efficiency and a low discharge / charge voltage platform. The porous carbon material with a larger pore structure exhibits high reversible capacity, high and low potential platforms, excellent cycle stability and high rate performance at low temperatures after pore regulation.
[0090] Finally, the carbon materials after pore regulation prepared in Examples 1 to 4 were subjected to nitrogen adsorption and desorption performance tests to obtain nitrogen adsorption and desorption curves of the carbon materials after pore regulation in Examples 1 to 4, as shown in FIG. Figure 7 As shown. Figure 7 It can be obtained that in the low pressure zone, the pore-regulated carbon materials prepared in Examples 2, 3, and 4 rise rapidly, indicating that they contain a large number of micropores. In the medium pressure zone, the pore-regulated carbon material prepared in Example 4 exhibits more mesopores and a large specific surface area.
[0091] It can be seen from the above embodiments that the present invention can control the pore type, pore volume, specific surface area, open pore size and surface interface state of the final carbon material by changing the type of carbon precursor, solution concentration, heat treatment temperature and pressure, and carbonization treatment temperature and heating rate. The regulated carbon material is conducive to the closed-pore filling of sodium ions, thereby optimizing the battery performance. The obtained material is used as a negative electrode material for sodium ion batteries, which can achieve a significant improvement in the low potential platform, the first coulombic efficiency, the rate performance, and the cycle stability, and also has excellent capacity retention in a low temperature environment.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for controlling the pores of a porous carbon material, characterized in that: It includes the following steps: The carbon precursor, solvent and porous carbon material are mixed to obtain a mixed solution; the mixed solution is subjected to heat treatment and carbonization treatment in sequence to complete the pore regulation of the porous carbon material.
2. The pore control method of porous carbon material according to claim 1, characterized in that: The carbon precursor includes one or more of coal tar, petroleum tar, chitosan and phenolic resin; The solvent includes one or more of tetrahydrofuran, xylene, n-hexane, ethanol and pyridine; The specific surface area of the porous carbon material is 20 to 5000 m 2 / g.
3. The pore control method of porous carbon material according to claim 1 or 2, characterized in that: The mass volume ratio of the carbon precursor, the solvent and the porous carbon material is 1g:10-30mL:0.01-10g.
4. The pore control method of porous carbon material according to claim 3, characterized in that: The heat treatment pressure is -0.01 to -10 MPa.
5. The pore control method of porous carbon material according to claim 4, characterized in that: The temperature of the heat treatment is 30-200° C., and the time of the heat treatment is 0.5-48 hours.
6. The pore control method of porous carbon material according to claim 5, characterized in that: The carbonization treatment is carried out under an inert atmosphere, which is nitrogen or argon.
7. The pore control method of porous carbon material according to claim 1 or 6, characterized in that: The pressure of the carbonization treatment is -5 to 0.1013 MPa.
8. The pore control method of porous carbon material according to claim 7, characterized in that: The heating rate of the carbonization treatment is 0.5-20°C / min, the target temperature of the carbonization treatment is 1100-2000°C, and the insulation time after reaching the target temperature is 0.5-8h.
9. A pore-controlled carbon material obtained by the pore-control method for a porous carbon material according to any one of claims 1 to 8.
10. Use of the pore-controlled carbon material according to claim 9 in negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Nitrogen-doped hierarchical pore carbon material as well as preparation method and application thereof
CN115285966A
Preparation method and application of asphalt-based hard carbon microsphere sodium storage material
CN116553511A
Preparation method of coal-based carbon material for sodium ion battery negative electrode
CN118343755A
One-step pressure-induced coal-based compact hard carbon negative electrode material, preparation method thereof and low-temperature sodium ion battery
CN118723974A
Activated carbon material, preparation method thereof and application of activated carbon material for preparing hard carbon negative electrode active material
CN118782790A